Dowsing for health tuning in to the earth's energy for personal development and wellbeing - MacManaway, Patrick (Lorenz Books, 2001)
This innovative new book explains the many different aspects of dowsing, from healing ourselves and others, to finding an re-patterning blocked energy paths.